THE CONTRIBUTION OF ADVAITA VEDANTA TO THE QUEST FOR AN EFFECTIVE REASSERTION OF THE ETERNAL: . - Schultz, Walter (Journal of Dharma, 1991)
An occidental disease has infested the global surface of human ,affairs, and we must now ask ourselves if we shall allow it to permeate the vital organs of mankind, l.e.. the great human traditions which sustain civilised activity on the surface. This disease, the empirical symptoms of which are rapidly becoming legion, from the gas chambers of Nazi Germany to the abortion clinics and snipers' bullets which assail us today, appears to be primarily a disease of the mind. Fostered in the occident, this disease entails a break with the classical attitude of the occident.